The Role of Mothers as Single Parents in Making Children with Disabilities Independent - Sunan, Moch Ilham Noer; Prasetyo, Franciscus Adi; Zuhudia, Primahesti Gitri (JURNAL IBU DAN ANAK, 2023)
Parents are the first place where individuals interact with their social environment, thus determining how the individual's personality is formed. There are problems related to the mother's role as a single parent in providing independence for children with disabilities. These problems include not understanding the knowledge and skills in accompanying children with disabilities, as well as not having relationships with parents who have experience with children with disabilities. Mothers as single parents also do not accept the condition of their children with disabilities, so they tend to provide negative parenting towards their children. This research approach uses qualitative case studies. To determine the location, use a purposive area at the Wing Mother Foundation Disability Services Unit, Banten Branch (UPD YSIB). The technique for determining informants uses purposive sampling with five main informants and one additional informant. Data collection techniques include observation and interviews. The results of this research explain the background of the mother's life as a single parent, the background of the child's disability, the role of the single parent, and the condition of independence of children with disabilities from before to after joining the support group at UPD YSIB. In the discussion, this research explains the role of mothers as single parents when they still experience obstacles and after making efforts to increase their knowledge and skills when joining the support group at UPD YSIB as well as changes in the independence of children with disabilities.